(untitled) (Heritage, 2025)
The paper presents the situation on the border of the Kruševac district in the period after the abdication of Prince Miloš until the establishment of the era of constitutional defenders and the time of Prince Aleksandar Karađorđević. The Kruševac district was on the border and this led to constant incursions by Turks and Arbanas, which were reflected in illegal crossings, unauthorized trade, non-compliance with quarantine rules, cattle theft, which was at its peak in this period, but continued during the entire rule of the defenders of the constitution. Jošanički and Koznički srez were especially threatened, but the situation was no better in Bugar Moravski and Kruševac srez. The Serbian authorities reacted, informed the representatives of the official Ottoman authorities, but also tried in all other ways to preserve their territory, and thus their autonomy.